How universal are IT project success and failure factors? Evidence from Hungary - Aranyossy, Márta; Blaskovics, Bálint; Horváth, Ákos Ardzsuna (Information systems management, 2018)
This article examines the universality of IT project failure factors and project manager characteristics for success - considering national cultural context, gender, experience and time. Based on a survey of 124 Hungarian IT professionals the comparative analysis concludes that stakeholder management, top management support and planning are the most critical factors of failure, whereas project managers with outstanding communication and change management skills are expected to excel - in Hungary and in the US as well.